Advances and Challenges of Fe-MOFs Based Materials as Electrocatalysts for Water Splitting. (September 2020) - Yang, Min; Zhou, Ya-Nan; Cao, Yu-Ning; Tong, Zhi; Dong, Bin; Chai, Yong-Ming
Highlights: Fe-MOFs based materials are the promising electrocatalysts for water splitting. Fe-based MOF, Fe-MOFs derivatives and their hybrids have been summarized. The current opportunities of Fe-MOFs based materials for water splitting are introduced. Abstract: Metal-organic frameworks (MOFs) have emerged as promising functional materials for electrocatalytic water splitting in view of their satisfactory properties, involving diversity in metal centers and organic ligands, as well as highly adjustable structures. In particular, Fe MOFs are attracting much more interest among various MOFs materials owing to the abundant resource and low toxicity of iron elements. Herein, we present the up-to-date advances and challenges of Fe-MOFs based materials as electrocatalysts for water splitting. The several key factors about limiting the improvements of Fe-based MOF and Fe-MOFs derivatives for water splitting are discussed in details. Next, on account of intrinsically poor conductivity and stability inheriting from pristine Fe MOFs, some recent modulation strategies towards water splitting have been summarized accordingly to the following three categories: Fe-based MOF, Fe-MOFs derivatives and their hybrids. The dispersion of active sites, element doping, conductive substrate have usually been adopted. Finally, this review briefly puts forward the current opportunities and challenges of Fe-MOFs based materials, along with several targeted solutions towards highly efficient water splitting. The advances and summary of Fe-MOFs based materials also may provide the guidance and implication for other catalytic process, energy storage and conversion. Graphical abstract: Image, graphical abstract